2021
DOI: 10.1109/jstars.2021.3119382
|View full text |Cite
|
Sign up to set email alerts
|

Possible Atmosphere and Ionospheric Anomalies of the 2019 Pakistan Earthquake Using Statistical and Machine Learning Procedures on MODIS LST, GPS TEC, and GIM TEC

Abstract: Identifying atmospheric and ionospheric anomalies based on remote sensing satellites has contributed highly to develop the hypothesis of lithosphere-atmosphere-ionosphere coupling (LAIC) over the Earthquake (EQ) epicenter during the seismic preparation period. This paper has investigated the variations of potential EQ precursor in daytime and nighttime Land Surface Temperature (LST) before and after the 2019 Pakistan EQ from MODIS (Moderate Resolution Imaging Spectroradiometer) satellite. The nighttime LST val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…These are better captured and exposed by the albedo, which is a sensitive index to the Earth's surface reflectance. Darker surfaces such as water and forests have a much lower albedo, and, consequently, more incident solar radiation is absorbed [67][68][69][70][71][72]. However, in our study, it was observed that the highest albedo values were directly related to exposed soil, while lower albedo values were directly related to the Amazon forest (Figure 3), as this is a more intense active agent in the absorption of water in Amazon biome.…”
Section: Discussionmentioning
confidence: 51%
“…These are better captured and exposed by the albedo, which is a sensitive index to the Earth's surface reflectance. Darker surfaces such as water and forests have a much lower albedo, and, consequently, more incident solar radiation is absorbed [67][68][69][70][71][72]. However, in our study, it was observed that the highest albedo values were directly related to exposed soil, while lower albedo values were directly related to the Amazon forest (Figure 3), as this is a more intense active agent in the absorption of water in Amazon biome.…”
Section: Discussionmentioning
confidence: 51%
“…In this study, multiple LAIC anomalies were confirmed using a nonlinear autoregressive with exogenous inputs (NARX) network for both the EQs. In the artificial neural network, NARX represented a nonlinear dynamic time series system [14,44]. Using the NARX network architecture for a time series, the independent input signal and output signal were regressed against the dependent output signal y (t) estimation.…”
Section: Anomaly Detection Using Neural Networkmentioning
confidence: 99%
“…These disturbances can be observed generally within 20 days before and/or 10 days after the main shock in the atmosphere, and this is followed by a significant variation within 5 days before and after in the ionosphere, which serve as EQ precursors. In the main, possible atmosphere and ionosphere anomalies can be observed in three regions from the satellite observations over the epicenter of the Earth's surface [12][13][14][15][16][17][18]. However, statistical analyses have showed that positive anomalies are more prominent than negative ones that have shallow hypocentral depth and large magnitude [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is still no clear demarcation of seismic precursors with remotely sensed data to clearly depict the location and occurrence of an earthquake event on a specific day. The seismic-induced anomalies exhibit positive and negative deviations beyond the prescribed bounds in various data of the lithosphere, atmosphere, and ionosphere [14,15]. The lithosphere experiences numerous geophysical changes as the earthquake's energy first interacts with this layer, generating possible precursors around the epicentral region of the earthquake [16].…”
Section: Introductionmentioning
confidence: 98%